The counter-reformation in the Catholic church. (16th Century.) - Beeman, Atwood N. H. (My University, 1905)
Introduction: In considering the Counter -reformation in the Catholic Church, it will be necessary briefly to look to the conditions of Church and people preceding that movement, and to the causes leading up to it. The Renaissance had spread from sunny Italy to her European neighbors, opening to the people new avenues of thought and action. Having been hitherto under restraint, they sought to break away from the authority that galled them. Wickliffe had stirred the English people with his utterances against the arrogance of the popes, declaring them to be antichrist (1377). He declared that Christ was the King of the Church. He denied the right of the popes to English territory. His teachings spread to the continent, and John Huss, in Bohemia (1412), demanded a reconstruction of the Church, after a thorough search of Holy Writ for the actual bases of Christianity, the Scriptures to be used as final authority. He insisted that an honest effort be made to satisfy all the requirements of soul and conscience. He and others found many reasons why such demands should be made. The immorality and worldliness of the popes had again and again scandalized the Old World. The clergy had become a separate caste, making and administering their own laws. Exempt from lay interference, they could escape punishment for the most flagrant violations of state law. Yet they would not exempt the laity from the laws of the Church, even though; the power they now had and the privileges they enjoyed had originally come from the people, whom they now oppressed.
Citation: Beeman, Atwood N. H. The counter-reformation in the Catholic church. (16th Century.). Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Counter-Refermation; Renaissancce; Wyckliffe and Huss; Conflict of Laws of Church and State; Theses